Effects Of Dashmula Tail Abhyanga And Dashmula Kwath Nadi Sweda In Sandhigata Vata :A Review Article - Chaturvedi, Uttam kumar; Rai, Lata (International Research Journal of Ayurveda & Yoga, 2021)
In the current situation, Vatavikara is the most serious health problem. Sandhigata Vikara, in particular, is found in large numbers in parts of India. Because of degenerative changes in joints, people over the age of 40 in our country face a serious problem with osteoarthritis. The degenerative changes are often caused by certain specific behaviours. Ayurveda is a holistic life science that focuses on an individual’s physical, social, and spiritual well-being. This science has well-explained the modalities of preventive and curative healthcare and can provide systematic solutions to humanity’s multifactorial diseases. Osteoarthritis (OA) is one such disorder that is on the rise as a result of poor diet and lifestyle choices. In medical science, there is no alternative to taking painkillers or having a knee replacement, but in Ayurveda, a variety of treatments are used to relieve pain and repair bones. Reduced stiffness and pain were observed after abhyanga (massage) with Dashmool Taila and application of Nadi Sweda, as it relaxes muscles and provides symptomatic relief in osteoarthritis. The aim of this paper is to highlight Ayurvedic steps in OA, specifically Abhyanga and Nadi Sweda.